El Excentrico, 1961-04-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 20, 1961 [20 de abril de 1961]. Ano 11, No 13. Cover has photograph of 1960's Miss California winner in royal attire. The headline reads, "Elite's Bathing Beauty Contest, Mary Ann Gardens, Sat May 13."